Emerging Threat: A Comprehensive Review of Crimean-Congo Haemorrhagic Fever Virus and Its Tick-Borne Transmission - Dr. Rajashree B. Patwardhan; Shikha R. Kumari; Malay Katariya (International Journal of Scientific Research in Science, Engineering and Technology, 2025)
India has emerged as a hotspot for emerging viral diseases, including the Crimean-Congo Hemorrhagic Fever Virus (CCHFV), which poses significant threats to public health and economic stability. Globalization, environmental changes, and increasing human-animal interactions have facilitated the transmission of zoonotic pathogens such as CCHFV, primarily transmitted through Hyalomma ticks and infected animal blood. CCHF is classified as a Biosafety Level-4 pathogen with outbreaks reported in over 30 countries. Its tripartite RNA genome comprises small (S), medium (M), and large (L) segments, encoding nucleoproteins, glycoproteins, and RNA polymerase, respectively. Clinical progression includes incubation, pre-hemorrhagic, hemorrhagic, and convalescent phases, with high mortality rates due to multiorgan failure and coagulopathies. Coinfections with diseases like malaria and dengue further complicate diagnosis and management. Current diagnostic methods include RT-PCR, ELISA, viral culture, and serological assays, though these require advanced infrastructure. The lack of approved vaccines or antiviral treatments intensifies the urgency for early detection and intervention. Rapid Diagnostic Tests (RDTs), though promising for field deployment, remain underdeveloped for CCHF. Diagnostic challenges are exacerbated by the virus’s similarity to other febrile illnesses, posing a risk of misdiagnosis. Effective containment requires enhanced biosafety measures, robust surveillance of animal reservoirs, and development of point-of-care diagnostics. Global cooperation, particularly through WHO-led initiatives, is vital to address this biosecurity concern. Comprehensive surveillance, increased diagnostic accessibility, and targeted public health strategies are essential to curb the spread of CCHFV and mitigate its potential use as a bioterrorism agent.